SUSTAINABLE FISHERIES IN SOUTHEAST ASIA - Ariadno, Melda Kamil (Indonesia Law Review, 2011)
Fisheries activity has increased significantly in number. As a result, we might see high investment in fisheries is due to the high demand for fish and fisheries products. Therefore, marine resources as well as other living resources are at risk in being harmed by excessive fisheries activities, for example: the use of trawl. Indonesia, as a Maritime State, need to impose sustainable fisheries because the principle of utilizing sustainable fisheries resources as adopted in the Law on Fisheries (Law No. 31 Year 2004 as amended by Law No. 45 Year 2009) to control fishery activities.Fishery activities are regulated not only by the Law on fisheries but also international regulation adopted worldwide such as the Code of Conduct for Responsible Fisheries (CCRF). CCRF was prepared to include primary principles to elaborate the mechanism of fishery activities which is designated not to cost harmful damages in fisheries activities. CCRF is also accompanied by several technical guidelines that provide certain procedures to be applied to (1) fishing operations; (2) the precautionary approach as applied to capture fisheries and species introductions; (3) integrating fisheries into coastal area management; (4) fisheries management; (5) aquaculture development; and (6) inland fisheries. Consequently, CCRF is intended to cover any kind of fishery anywhere in the world not just marine capture fisheries, but also freshwater fisheries as well as aquaculture both marine and freshwater aquaculture. Excessive fishery activities would then not be harmful if Indonesia is willing to impose regulation which is significantly and effectively to manage these kind of fishery activities. Along with the fact that Indonesia is recognized as a Marine State, there is no reason to hold back in addressing this situation.